Morbidity pattern among school going adolescent girls of a North Indian district - Sachan, Beena; Idris, M. Z.; Kumari, Reema; Jain, Savita; Singh, Ashutosh (International Journal Of Community Medicine And Public Health, 2017)
Background: The objective of the study was to assess the morbidity pattern among school going adolescent girls in Lucknow district of North India. Methods: A cross-sectional study was carried out in urban and rural schools of Lucknow district. Multistage random sampling was used to select the requisite number of girls. A total of 847 adolescent girls between 10 and 19 years of age were interviewed and examined physically from head to toe and any signs and symptoms of illness were recorded. Statistical analyses were done using percentage and Chi-square test. Results: Of 847 adolescent girls, around 64.8% were found to be sick at the time of the study. A maximum of 16.4% girls were suffering with hair problems followed by teeth and gum problems, which was 14.2%. 56.3% girls were suffering with iron deficiency and 0.5% girls with vitamin A deficiency. Riboflavin deficiency was statistically more (2.8%) in rural schools when compared to urban school girls (0.7%). Conclusions: This study reveals a high prevalence of morbidity. A strong need exists for planning and programming intervention activities for health needs in the area.